A Novel Type-I Interferon Family, Bovine Interferon-Chi, Is Involved in Positive-Feedback Regulation of Interferon Production - Guo, Yongli; Song, Zhifeng; Li, Chenfeng; Yu, Yueyang; Dai, Haiyue; Luo, Xiuxin; Wang, Yujiao; Wang, Junwei; Gao, Mingchun (Frontiers in Immunology, 2020)
Interferon-chi (IFN-χ) is a type of function-unknown IFN. IFN-χ in bovines (BoIFN-χ) has evolved as a multigene family. This family comprises four IFN-χ subtypes, two of which are functional genes, which we demonstrated to: (i) have antiviral and antiproliferative activities; (ii) be highly sensitive to trypsin; (iii) remain stable with changes in pH and temperature. BoIFN-χ is a key intermediate in antiviral response, PAbs against BoIFN-χs could downregulate the transcriptional activation of ISGs induced by poly(I:C), and BoIFN-χs could be induced upon virus infection at the early and late phase. Additionally, BoIFN-χs bind with type-I IFN receptors, induce transcription of interferon regulatory factor 7 (IRF7), interferon-stimulated genes (ISGs), and type-I IFNs, as well as myxovirus resistance protein 1 (Mx1) expression. Expression of ISGs and activity of interferon-stimulated response element (ISRE) induced with BoIFN-χs could be downregulated significantly by the Janus kinase (JAK) 1 and signal transducers and activators of transcription (STAT) 1 inhibitor. The promoters of BoIFN-β, nuclear factor-kappa B, and ISRE could be activated with BoIFN-χs, and the BoIFN-χ promoter could be activated by other type-I IFNs. Overall, BoIFN-χ could be induced with virus infection and signal through the JAK-STAT pathway to form a positive-feedback regulation of IFN production. These findings may facilitate further research on the role of IFN-χ in innate immune responses.